MEDIEVAL SCIENTISTS OF THE SCIENCE OF BALAGAT - Salima Rustamiy Aliybeg qizi (Galaxy International Interdisciplinary Research Journal, 2024)
In development of Human civilization, besides the “exact” sciences, there was a strong demand for the study of the Qur’ān which covered such issues as interpretation, jurisprudence, beliefs and philology. The linguistic views covering theoretical and practical issues have developed in the structure of the philological sciences as a set of multibranch and complex scientific theories like vocabulary, morphology, syntax, the art of speech and its object of study has become the language, linguistic phenomena and the speech, the expression of language. The language has been estimated as a system of complex symbols.